Parakratos: Narratives of Political and Military Conspiracies in Modern Greek Historiography - Tohma, Nikola (Karolinum, 2025)
This book analyzes the conspiratorial concept of parakratos (translated as "deep state" or "parastate") as a Cold War parallel power mechanism that exerted a profound influence on the political landscape in post-civil war Greece (1949-1967). A well-known phenomenon to the Greek domestic public, the far right parakratos became the usual suspect for political murders, election rigging, and terrorism during this period. Despite its notoriety for numerous outrageous incidents, including the assassination of the left-wing politician Grigoris Lambrakis in Thessaloniki in 1963, the structure of the parakratos has eluded a comprehensive understanding, primarily due to the paucity of reliable sources and the absence of a scholarly consensus regarding its nature. Parakratos endeavors to problematize the current conception of parakratos by underscoring the capacity of the concept to not only represent but also define and transform the Greek domestic Cold War politics and our perception of it. Rather than seeking to explain the presumed conspiracies typically ascribed to the groups and members, the book aims to demonstrate how these events influenced the domestic and international politics of the era and thereby contributed to the establishment of a legacy of conspiracy theories as a means of political struggle. Moreover, it connects the Greek parakratos to the broader debate on parapolitics as well as the concepts of the dual state, the security state, and the deep state in various national contexts.
Keywords: Politologie